Empowerment of South African youth through identity change - Hajji, Jaida (My University, 2019)
People’s identity may be shaped through schools and universities. Heleta (2016) talks about an “epistemic violence” (Heleta, 2016, p. 5) that maintains the hegemony of White identity through schools and universities. In South Africa, the actual pedagogy used at schools and universities can belittle Black South African youth, by constructing a White valued identity that opposes a Back subordinated identity. If schools and universities can belittle Black South African youth, they can also empower them by adopting a new pedagogy. South African youth can adopt a subordinated identity because of people’s discourses, practices and attitudes (Annamma, Connor & Ferri, 2013). If Black South African youth can have a negative and subordinated identity through people’s discourses, practices and attitudes – they can also have a positive and valued identity through a certain type of discourse, practice and attitude. Freire’s pedagogy gathers, through the notion of love, these three key elements in terms of dialogue (discourse), sacrifice (practice) and trust (attitude). According to Freire (1996), this empowering triptych refers to a change of identity from oppressor or oppressed to humanist, from non-human or semi-human to fully human, and from subordinated identities to valued identities – which then leads to awareness. Freire’s pedagogy of love may be helpful for Black South African youth – to construct a valued identity and to improve their chances of achieving positive educational outcomes through awareness. In South Africa, the YCS (Young Christian Students) community frames their actions and thinking process according to Freire’s pedagogy (named Freire’s pedagogy of love in this research) to empower South African youth. In this research, the YCS community gathering young South African students, was interviewed. According to the South African YCS community, Freire’s pedagogy of love has a positive impact on their identity by empowering them in respect of emotional balance, and individual and social dimensions. Thus, this research provides a new pedagogy that may change the actual and unfair dynamics in South African schools and universities through identity change
A research report submitted to the School of Education, Faculty of Humanities, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the Masters degree in Education by coursework